Evaluation of "Golden Proportion" in Saudi individuals with natural smiles - Amal Ali Swelem; Eman MohamedZaghloul Al-Rafah (Elsevier, 2019)
Background: The Golden Proportion (GP) has been considered by many as the most harmonious recurrent tooth-to-tooth ratio and has long been proposed as an aesthetic guideline for restoring/replacing maxillary anterior teeth. Researchers investigated GP in various populations. Purpose: The aim of the current study was to investigate the occurrence and prevalence of the GP between the perceived widths of maxillary anterior teeth in a Saudi population with natural smiles. Materials and Methods: A total of 360 Saudi dental students (180 males and 180 females) with natural smiles and who met the inclusion criteria were included in the study. Frontal photographs were captured for all participants while maximally smiling using a digital camera with standardized settings. Photo-editing software was used to measure the perceived mesiodistal width of each anterior maxillary tooth in all digital images. Paired and student t-tests were performed to detect side and/or gender differences respectively. Calculated ratios of the perceived mesiodistal widths of the teeth were compared with their respective GP values using a one sample t-test. Statistical significance was set at 5%. Results: For both genders, there were significant differences (P < 0.001) between the calculated ratios and the golden ratios. No side differences in the GP were detected. Males had wider teeth than females however significant differences between genders was detected for the centrals (P < 0.001) only. Conclusions: Width ratios of the maxillary anterior teeth did not follow the GP for the examined Saudi population. Males had wider anterior teeth with the centrals exhibiting a significant gender-based difference. There was no side-dependent variation for both genders.